Dampak media sosial dan perilaku kenakalan remaja terhadap interaksi sosial - Ulum, Ilsa Fikrotul (Maliki Interdisciplinary Journal, 2024)
Social media is a platform or collection of applications that allows users to share various things with the wider community at a global level. As an online medium, social media can be used by people to interact and communicate online, which can be accessed from anywhere and at any time, without distance restrictions. However, excessive and uncontrolled use of social media can influence user behavior negatively. It cannot be denied that social media has a big influence on a person's life. Someone who was initially unknown can become famous thanks to social media, and vice versa. Especially among teenagers, social media has become an addiction that makes them unable to get away from it, to the point where they lose track of time. For teenagers who are still in the phase of finding their identity, social media will certainly influence them through the content or posts they access. Therefore, there needs to be limits and supervision when someone uses social media. This research uses the literature review method. This research finds out the impact of social media on teenagers. This research found the positive and negative impacts of social media. The impact The positive thing is that it can increase cooperation, build relationships as a learning tool, a place to develop skills and expand your network of friends. The negative impact is that face-to-face interactions reduce a lot of crime in cyberspace.